Menggereja yang Ramah dalam Ruang Virtual: Aktualisasi Iman Kristen Merawat Keragaman - Yonatan Alex Arifianto; Carolina Etnasari Anjaya (Sekolah Tinggi Teologi Baptis, Jakarta, 2022)
In living in a virtual space, believers are required to be able to influence the values and patterns that are formed in accordance with the values of the Christian faith. The research aims to convey the principles or models of friendly church life and practical ways of carrying them out in virtual space life within the framework of religious moderation. The research method is a descriptive qualitative approach through literature study. The research concludes that a friendly church becomes a necessity for believers as a fulfillment of God's command to bring shalom and leave this world with elements of Christian faith values. The principle of a friendly church is the awareness to love God through acts of love for others and the synergy of believers in one unit, faith, and purpose in life. The praxis of a friendly church can be actualized with virtual social services in the context of contemporary issues. Believers are required to be present as a solution to various social problems. This will reduce the turbulence of the virtual space with a tendency to wickedness. This praxis can run optimally if it is supported by the synergy of believers in collaboration with various crosses: denominations, communities, professions, competencies, and generations. AbstrakDalam kehidupan di ruang virtual umat percaya dituntut untuk dapat memberikan pengaruh atas nilai-nilai dan pola yang terbentuk sesuai dengan nilai-nilai iman Kristen. Penelitian bertujuan menyampaikan prinsip atau model hidup menggereja yang ramah dan cara praksis menjalankannya dalam kehidupan ruang virtual dalam bingkai moderasi beragama Metode riset adalah pendekatan jenis kualitatif deskriptif melalui studi pustaka. Riset memberikan simpulan bahwa menggereja yang ramah menjadi suatu kebutuhan bagi umat percaya sebagai pemenuhan perintah Tuhan untuk membawa shalom dan mengkhamirkan dunia ini dengan unsur nilai iman Kristen. Prinsip menggereja yang ramah adalah kesadaran untuk mengasihi Tuhan melalui tindakan kasih kepada sesama dan sinergitas umat percaya dalam satu kesatuan wadah, iman dan tujuan hidup. Praksis menggereja yang ramah dapat diaktualisasikan dengan pelayanan sosial virtual dalam lingkup isu-isu kontemporer. Umat percaya dituntut untuk hadir sebagai solusi bagi pelbagai persoalan sosial. Hal ini akan meredam gejolak ruang virtual yang bertendensi pada kefasikan. Praksis tersebut dapat berjalan optimal jika didukung oleh sinergitas umat percaya dengan kolaborasi pelbagai lintas: denominasi, komunitas, profesi, kompetensi, dan generasi.